A Wide‐Range Photosensitive Weyl Semimetal Single Crystal—TaAs. Issue 43 (10th September 2018) - Chi, Shumeng; Li, Zhilin; Xie, Ying; Zhao, Yongguang; Wang, Zeyan; Li, Lei; Yu, Haohai; Wang, Gang; Weng, Hongming; Zhang, Huaijin; Wang, Jiyang
Abstract: Mid‐ and even long‐infrared photodetection is highly desired for various modern optoelectronic devices, and photodetectors that operate at room temperature (RT) remain challenging and are being extensively sought. Recently, the Weyl semimetal has attracted much interest, and its Lorentz invariance can be broken to have tilted chiral Weyl cones around the Fermi level, which indicates that the photocurrent can be generated by the incident photons at arbitrarily long wavelengths. Furthermore, the atypical linear dispersion bands in Weyl cones result in high carrier mobility and quadratic energy dependence of the density of states, which can enhance the efficiency of the photocurrent and suppress thermal carriers, in addition to its favorable large absorption coefficient. In this study, a Weyl semimetal TaAs photodetecting prototype is reported, which operates at RT with an outstanding response that ranges from the visible to the long‐infrared range. This study indicates that the Weyl semimetal TaAs should boost the development of modern optoelectronics and photonics. Abstract : Facing the challenge of mid‐ and long‐infrared photodetection at room temperature, an ultrabroadband photodetecting prototype made by the Weyl semimetal TaAs single crystal is proposed, which can operate from the visible 438.5 nm to the long‐infrared 10.29 µm with an outstanding response at room temperature. Furthermore, the linear dispersion bands in Weyl cones can enhance the efficiency of the photocurrent.